ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI WANITA KARIER DALAM POLA ASUH PENDIDIKAN ANAK DI KOTA PONTIANAK - Sunarsih Sunarsih; Desvira Zain; Ismail Umar (Inovbiz: Jurnal Inovasi Bisnis, 2018)
In the globalization Era, it is word wide accepted that the total of carier women is significant in numbers, in accordance with Educational level, they could have important, positions. They could work in many areas, even higher than men workers. Thus, this is be coming challenges for married and carier women as well raising children. Current research entitles analysis of determinant factors of carier women on raising children pattern in Pontianak. Carier women and having chidren are charged as research respondens and as many as 6o respondents randomly taken, as others criterions working in private sectors, single carier maried women with children. Linier regression analysis is used to analyze the data, the findings showed that, the internal factors show a strong significant factor to affect the carier women on raising children pattern 73,9%, while 26,1% was inflrenced by the external factors. Statistical output also described that women level educations plays crucial role in raising chidren pattern.